The closer the better: Does better access to outpatient care prevent hospitalization? - Peter S. Elek; Tamás Molnár; Balázs Váradi (Hungarian Academy of Sciences, Institute of Economics, 2018)
In 2010-2012 new outpatient service locations were established in poor Hungarian microregions. We exploit this quasi-experiment to estimate the extent of substitution between outpatient and inpatient care. Fixed-effects Poisson models on individual-level panel data for years 2008-2015 show that the number of outpatient visits increased by 19% and the number of inpatient stays decreased by 1.6% as a result, driven by a marked reduction of potentially avoidable hospitalization (PAH) (5%). In our dynamic specification, PAH effects occur in the year after the treatment, whereas non-PAH only decreases with a multi-year lag. The instrumental variable estimates suggest that a one euro increase in outpatient care expenditures produces a 0.6 euro decrease in inpatient care expenditures. Our results (1) strengthen the claim that bringing outpatient care closer to a previously underserved population yields considerable health benefits, and (2) suggest that there is a strong substitution element between outpatient and inpatient care.
Keywords: C23; C26; I10; 330; Administrative panel data; Inpatient care; Outpatient care; Potentially avoidable hospitalization; Quasi-experiment; Substitution effect